Identification of novel molecular subtypes and a signature to predict prognosis and therapeutic response based on cuproptosis-related genes in prostate cancer - Zhang, Jili; Jiang, Shaoqin; Gu, Di; Zhang, Wenhui; Shen, Xianqi; Qu, Min; Yang, Chenghua; Wang, Yan; Gao, Xu (Frontiers in Oncology, 2023)
Abstract: Prostate cancer (PCa) is the most common malignancy of the male urinary system. Cuproptosis, as a novel regulated cell death, remains unclear in PCa. Here, consensus clustering analysis identified two cuproptosis-related molecular subtypes with significant differences in prognoses, clinical features, and immune profiles based on cuproptosis-related genes. Then, a prognostic signature comprised of five genes (B4GALNT4, FAM83D, COL1A, CHRM3, and MYBPC1) was constructed based on differentially expressed genes between the two subtypes through LASSO cox regression analyses with 10-fold cross-validation. This signature was further validated in eight external datasets. Next, the tumor microenvironment, immunotherapy prediction, somatic mutation, chemotherapy response prediction, and potential drug prediction were also analyzed based on the risk signature. Finally, the expression and regulation of these model genes were explored by qRT-PCR, and transcriptomics and proteomics analyses revealed that the key model gene B4GALNT4 might regulate cuproptosis-related genes (CRGs) through protein modification after transcription. In conclusion, the cuproptosis-related molecular subtypes and the prognostic signature identified in this study could be used to predict the prognosis and contribute to the clinical decision-making of PCa. Furthermore, we identified a potential cuproptosis-related oncogene B4GALNT4 in PCa, which could be used as a target to treat PCa in combination with cuproptosis.